Cancer induces cardiomyocyte remodeling and hypoinnervation in the left ventricle of the mouse heart - Mühlfeld, Christian; Das, Suman Kumar; Heinzel, Frank R.; Schmidt, Albrecht; Post, Heiner; Schauer, Silvia; Papadakis, Tamara; Kummer, Wolfgang; Hoefler, Gerald; Justus Liebig University Giessen (My University, 2011)
Cancer is often associated with cachexia, cardiovascular symptoms and autonomic dysregulation. We tested whether extracardiac cancer directly affects the innervation of left ventricular myocardium. Mice injected with Lewis lung carcinoma cells (tumor group, TG) or PBS (control group, CG) were analyzed after 21 days. Cardiac function (echocardiography), serum levels of TNF-alpha and Il-6 (ELISA), structural alterations of cardiomyocytes and their innervation (design-based stereology) and levels of innervation-related mRNA (quantitative RT-PCR) were analysed. The groups did not differ in various functional parameters. Serum levels of TNF-alpha and Il-6 were elevated in TG. The total length of axons in the left ventricle was reduced. The number of dense core vesicles per axon profile was reduced. Decreased myofibrillar volume, increased sarcoplasmic volume and increased volume of lipid droplets were indicative of metabolic alterations of TG cardiomyocytes. In the heart, the mRNA level of nerve growth factor was reduced whereas that of beta1-adrenergic receptor was unchanged in TG. In the stellate ganglion of TG, mRNA levels of nerve growth factor and neuropeptide Y were decreased and that of tyrosine hydroxylase was increased. In summary, cancer induces a systemic pro-inflammatory state, a significant reduction in myocardial innervation and a catabolic phenotype of cardiomyocytes in the mouse. Reduced expression of nerve growth factor may account for the reduced myocardial innervation.
Keywords: cancer; hypoinnervation; cardiomyocyte remodling; left ventricular; mouse heart; ddc:610